Sustainability of Long-term Care: Puzzling Tasks Ahead for Policy-Makers - Ilaria Mosca; Philip J. van der Wees; Esther S. Mot; Joost J.G. Wammes; Patrick P.T. Jeurissen (Kerman University of Medical Sciences, 2017)
Background The sustainability of long-term care (LTC) is a prominent policy priority in many Western countries. LTC is one of the most pressing fiscal issues for the growing population of elderly people in the European Union (EU) Member States. Country recommendations regarding LTC are prominent under the EU's European Semester. Methods This paper examines challenges related to the financial- and organizational sustainability of LTC systems in the EU. We combined a targeted literature review and a descriptive selected country analysis of: (1) public- and private funding; (2) informal care and externalities; and (3) the possible role of technology in increasing productivity. Countries were selected via purposive sampling to establish a cohort of country cases covering the spectrum of differences in LTC systems: public spending, private funding, informal care use, informal care support, and cash benefits. Results The aging of the population, the increasing gap between availability of informal care and demand for LTC, substantial market failures of private funding for LTC, and fiscal imbalances in some countries, have led to structural reforms and enduring pressures for LTC policy-makers across the EU. Our exploration of national policies illustrates different solutions that attempt to promote fairness while stimulating efficient delivery of services. Important steps must be taken to address the sustainability of LTC. First, countries should look deeper into the possibilities of complementing public- and private funding, as well as at addressing market failures of private funding. Second, informal care externalities with spill-over into neighboring policy areas, the labor force, and formal LTC workers, should be properly addressed. Thirdly, innovations in LTC services should be stimulated to increase productivity through technology and process innovations, and to reduce costs. Conclusion The analysis shows why it is difficult for EU Member State governments to meet all their goals for sustainable LTC, given the demographic- and fiscal circumstances, and the complexities of LTC systems. It also shows the usefulness to learn from policy design and implementation of LTC policy in other countries, within and outside the EU. Researchers can contribute by studying conditions, under which the strategies explored might deliver solutions for policy-makers